Proficiency of South African intern doctors in recognising ischaemia on an electrocardiogram - Relisha K. Naidoo; Duncan M. Havenga; David Morris (Journal of the Colleges of Medicine of South Africa)
Background: Interpreting an electrocardiogram (ECG) is challenging for junior doctors, and proficiency gaps exist commonly worldwide. This study assessed interpretation accuracy and self-confidence of South African intern doctors in identifying acute myocardial ischaemia on an ECG and analysed the impact of an education strategy.